CD56, CD57, HBME1, CK19, Galectin-3 and p63 immunohistochemical stains in differentiating diagnosis of thyroid benign/malign lesions and NIFTP - Tastekin, Ebru; Keskin, Elif; Can, Nuray; Canberk, Sule; Mut, Ayse; Erdogan, Ezgi; Asa, Nurtac; Güldiken, Sibel; Sezer, Atakan; Azatcam, Meltem (Polish Journal of Pathology, 2019)
Detection of thyroid carcinoma has been steadily increased in the past few decades. After the recognition of NIFTP, also gain importance to differentiate benign tumors (follicular adenoma) from follicular patterned variants of papillary thyroid carcinoma (invasive and infiltrative follicular variant papillary thyroid carcinoma), and low-risk lesions of thyroid (NIFTP). Follicular patterned proliferations of thyroid still persists as a battle for pathologists. In this study, we aimed to analyze the most commonly used immunohistochemical stains “HBME1, CK19, Galectin-3”, adding the new ones “CD56, CD57, and p63”. Study groups were; nodular hyperplasia, follicular adenoma, NIFTP, infiltrative follicular variant PTC, classical variant PTC (CVPTC) and follicular carcinoma. Each group consisted of twenty cases. The sections were stained with CD56, CD57, p63, CK19, HBME1 (Mesotel cell), Galectin-3 antibody. Although the expression of CD56 was high in benign follicular lesions, FC could not be excluded in this group. CD57 was high in malignant follicular group and NIFTP. Interestingly, p63 was found highly expressed in FVPTC, which might be promising to predict invasiveness in follicular group of lesions. CK19, Galectin-3 and HBME1 were found quietly prominent in CVPTC in concordance with the previous reports.